Self-employment transitions at older ages in urban and rural labor markets - Hannu Tervo; Hannu Niittykangas (European Regional Science Association (ERSA), 2011)
Workforce is aging in most developed countries, but still needed in productive work. Entrepreneurship at older ages is an option for many aging individuals. As existing and future generations are healthier and more able to work than previous generations, working careers can, and also have been extended. Various reasons such as age, health, gender and education, family status, accumulated savings and organizational factors can affect the choice between full-time work, bridge employment and retirement. But bridge employment as well as career choices may also be affected by many environmental factors. Regions with strong traditions of entrepreneurship may be more favourable to bridge employment in the form of self-employment than other regions. On the other hand, demand conditions may also account for possibilities to bridge employment. Regions with a low level of demand may not be favourable to self-employment at older ages. While some studies have focused on transitions into self-employment among older workers, the question of the motives and background still need clarification. This paper analyzes those who start a business at older ages in different regions in Finland. Who are they, and what is their background? What is the effect of human and financial capital on self-employment decisions? What is the role of previous experience in entrepreneurship - are those without experience from entrepreneurship different from those who have it? Is self-employment at older ages a real alternative only for serial and habitual entrepreneurs? In the analysis, we utilize a large longitudinal micro data to examine transfers of workers and those out of employment aged 55-74 into self-employment in Finland in 1998-2004. The data set represents a 7 percent sample of all Finns in 2001 of whom we have a lot of register-based and other data even from the year 1970 onward. Note: An alternative choice was : theme N: enterpreuneurship, networks and innovation
Keywords: 330